2014
DOI: 10.1149/06106.0021ecst
|View full text |Cite
|
Sign up to set email alerts
|

Integrated CMOS-MEMS Technology and Its Applications

Abstract: The paper reports a feature and techniques to resolve requirements of integrated CMOS-MEMS technology. The multiphysics simulation platform for this technology has been developed to understand simultaneously both the mechanical and electrical behaviors of MEMS stacked on LSI. An equivalent circuit of a MEMS accelerometer has been developed with an electrical circuit simulator. We review the technology for CMOS-MEMS accelerometer with a wide detection range. Using the simulation platform above, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…6. (8)(9)(10) When acceleration is applied to the MEMS accelerometer, C s is changed. C p is capacitance in the SiO 2 film.…”
Section: Detection Of Accelerationmentioning
confidence: 99%
See 2 more Smart Citations
“…6. (8)(9)(10) When acceleration is applied to the MEMS accelerometer, C s is changed. C p is capacitance in the SiO 2 film.…”
Section: Detection Of Accelerationmentioning
confidence: 99%
“…(5)(6)(7) Thus, our group has developed MEMS accelerometers with sensing resolutions higher than 1 G (1 G = 9.8 m/s 2 ). (8)(9)(10) The performance of MEMS accelerometers is affected by noise, including the Brownian noise B n . (11)(12)(13)(14) In practical use, the sensing resolution of MEMS accelerometers is evaluated using vibration exciters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties make gold promising materials to be used as structure materials in micro-electro-mechanical systems (MEMS) devices. Yamane et al reported that the sensitivity of MEMS accelerometers using gold-based components would be higher when compared with the conventional silicon-based components [1][2][3] . The high sensitivity is mostly contributed by the much higher density of gold (19.30 g/cm 3 at 298 K) than silicon (2.33 g/ cm 3 at 298 K).…”
Section: Introductionmentioning
confidence: 99%
“…After the seed layer formation, lithography process and electroplating are carried out. More details can be found in the previous study [5]. The micro-cantilevers were fabricated on a SiO 2 layer.…”
Section: Introductionmentioning
confidence: 99%